Accounting Scandals in Malaysia and Stock Market Reactions - Lye, Boon Yee (2007)
Fraudulent financial reporting by companies is a matter of grave social and economic concern. In view of the recent occurrence of an unprecedented number of accounting scandals in Malaysia, it is of our concern to examine the stock market reaction to announcement of fraudulent financial reporting. The event study methodology of non-parametric rank test proposed by Corrado (1989) was used to determine the statistical significance of the excess returns in stock prices in event studies. The data was primarily collected via a comprehensive full-text search of the articles or reports in respect of accounting irregularities contained in the SC Press Releases and the SC Enforcement Actions from January 1998 to July 2007 which are accessible from the SC website. From the data collected, it was found that the number of cases of accounting scandals uncovered by the SC over the past decade generally followed the evolution of key milestones in DBR framework to enhance corporate governance standards. The event study findings were found to have experienced significant declines in prices immediately after the event date but failed to show a linkage between the announcement of accounting fraud and the market value of a company over the long-term. After the revelations of accounting irregularities, many of these companies are facing problems of insolvency, followed by numerous lawsuits or winding-up petitions filed by creditors and banks, and eventually many of them had been removed from the Official List of the BM. The role of the management, auditors and regulators in the detection of fraudulent financial reporting are explored and the effectiveness of the recent reform of laws in deterring the incidence of accounting irregularities are studied. The most common financial reporting violation was the inflation of revenue and/or earnings in order to meet market expectations. These findings provide important implications for public policy-makers in respect of their future efforts in preventing and/or reducing the occurrence of accounting fraud.